Modeling and Optimizing Service Quality Improvement (Empirical study uses the POP-HRM approach to training instructors Security Unit in Bogor Regency) - Uli Rohana Siregar; Soewarto Hardhienata; Sri Setyaningsih (International Journal of Business and Social Science Research, 2023)
This study aims to find ways and strategies to improve service quality by analyzing the influence of other variables on service quality. The other variables are organizational support, work motivation, job satisfaction, and work commitment. Furthermore, the methods and strategies for improving the quality of education and training services found were made recommendations to related parties, namely the Republic of Indonesia Police, leaders of education and training institutions, and training instructors for the Security Unit in Bogor Regency. The population is as many as 168 instructors of security training and training from 33 security training institutions, spread across 16 sub-districts in the Bogor Regency area. The research sample is 118 respondents. Data analysis used SITOREM analysis. The results of the study show 1) There is a direct positive effect of organizational support on service quality with a path coefficient (βy1) of 0.302, so that strengthening organizational support can improve service quality; 2) There is a direct positive effect of work motivation on service quality with a path coefficient (βy2) of 0.211, so that strengthening work motivation can improve service quality; 3) There is a direct positive effect of job satisfaction on service quality with a path coefficient (βy3) of 0.201, so that strengthening job satisfaction can improve service quality; 4) There is a direct positive effect of work commitment on service quality with a path coefficient (βy4) of 0.212, so that strengthening work motivation can improve service quality; 5) There is a direct positive effect of Organizational Support on job satisfaction with a path coefficient (βy31) of 0.432, so that strengthening organizational support can increase job satisfaction; 6) There is a direct positive effect of work motivation on job satisfaction with a path coefficient (βy32) of 0.535, so that strengthening work motivation can increase job satisfaction; 7) There is a direct positive effect of Organizational Support on work commitment with a path coefficient (βy41) of 0.553, so that strengthening organizational support can increase work commitment; 8) There is a direct positive effect of work motivation on work commitment with a path coefficient (βy42) of 0.412, so that strengthening work motivation can increase work commitment; 9) There is an indirect positive effect of organizational support on service quality through job satisfaction with a path coefficient (βx13y) of 0.091, so that strengthening organizational support can improve service quality through strengthening job satisfaction; 10) There is an indirect positive effect of work motivation on service quality through job satisfaction with a path coefficient (βx23y) of 0.113, so that strengthening work motivation can improve service quality through strengthening job satisfaction; 11) There is an indirect positive effect of organizational support on service quality through work commitment with a path coefficient (βx14y) of 0.087, so that strengthening organizational support can improve service quality through strengthening work commitment; 12) There is an indirect positive effect of work motivation on service quality through work commitment with a path coefficient (βx24y) of 0.117, so that strengthening work motivation can improve service quality through strengthening work commitment; 13) There is a direct positive effect of work motivation on organizational support with a path coefficient (βy12) of 0.852, so strengthening work motivation can increase work commitment.